Producción de tres variedades de pepino (cucumis sativus l.) con la aplicación de lixiviados en el cantón La Maná. - Castillo Peralta, Adonis José (2023)
The cucumber crop (Cucumis sativus L.) is considered a plant of great economic importance due to its high consumption rate that is consumed fresh and processed. For various regions of the world, it is known as a species whose agronomic value lies in its seasonal production. The objective was to evaluate the production of three varieties of one with the foliar application of leachate based on earthworm humus and bovine manure. An experimental design called completely randomized blocks (DBCA) was used, with nine treatments and three repetitions. The evaluated variables were subjected to the analysis of variance using the Tukey test at 5% to determine statistical differences between the treatments studied. The study distributed in agronomic and productive variables such as growth rate index, number of leaves, number of flowers/fruits, fruit length, fruit diameter, fruit weight, crop yield, and economic analysis, with the application of Earthworm humus leached (1.75 L/h) obtained great flowering and fruiting, with an average of 13,07 number of flowers/fruits. The size of the fruits was greater when applying Earthworm Humus Leachate (1.75 L / h) at 22,32 cm, the equatorial and polar diameter of 5,75 cm with the application of Bovine Manure Leachate (1.5 L/ h) obtaining the fruits exhibited greater weight when applying it with an average of 316,62 g. The yield per hectare was significantly higher when treating the plants with the application of earthworm humus with 18074.56 kg/h causing the production of more fruits, which had great weight. In conclusion, the high economic benefit provoked the cucumber production, with a 10.38% profitability for the Marketmore Cucumber variety.